Acetaldehyde Content and Oxidative Stress in the Deleterious Effects of Alcohol Drinking on Rat Uterine Horn - Lara Romina Buthet; María Eugenia Maciel; Leandro Néstor Quintans; Carmen Rodríguez de Castro; Martín Hernán Costantini; Silvia Laura Fanelli; José Alberto Castro; Gerardo Daniel Castro (Journal of Toxicology)
After alcohol exposure through a standard Lieber and De Carli diet for 28 days, a severe atrophy in the rat uteirne horn was observed, accompanied by significant alterations in its epithelial cells. Microsomal pathway of acetaldehyde production was slightly increased. Hydroxyl radicals were detected in the cytosolic fraction, and this was attributed to participation of xanthine oxidoreductase. They were also observed in the microsomal fraction in the presence of NADPH generating system. No generation of 1-hydroxyethyl was evidenced. The t-butylhydroperoxide-induced chemiluminescence analysis of uterine horn homogenates revealed a significant increase in the chemiluminiscence emission due to ethanol exposure. In the animals repeatedly exposed to alcohol, sulfhydryl content from uterine horn proteins was decreased, but no significant changes were observed in the protein carbonyl content from the same samples. Minor but significant decreasing changes were observed in the GSH content accompanied by a tendency to decrease in the GSH/GSSG ratio. A highly significant finding was the diminished activity content of glutathione peroxidase. Results suggest that acetaldehyde accumulation plus the oxidative stress may play an additional effect to the alcohol-promoted hormonal changes in the uterus reported by others after chronic exposure to alcohol.